Financial Distress dan Leverage pada Pengungkapan Sustainability Report - Putu Riska Narayani; Luh Gede Krisna Dewi (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
The research aims to empirically prove the influence of financial distress and leverage on sustainability report disclosure with media visibility as a control variable. Non-financial companies listed on the Indonesia Stock Exchange from 2018 to 2022 were chosen as the population for this study. Sample of 415 observations was selected using nonprobability sampling method with purposive sampling technique. Data in this research were analyzed using panel data regression analysis technique with Eviews 12. The research results indicate that financial distress has a negative effect on sustainability report disclosure. Leverage does not have an influence on sustainability report disclosure. Media visibility has a positive influence on sustainability report disclosure and needs to be maintained as a control variable.